Dipturus batis Linnaeus 1758 - Gordon, Cat A.; Hood, Ali R.; Ellis, Jim R. (Zenodo, 2016)
Dipturus batis (Linnaeus, 1758) Distribution. Blue (or grey) skate ( D. batis, the form described by Iglésias et al. (2010) as Dipturus cf. flossada ) generally has a more southerly distribution than Dipturus cf. intermedia (Parnell, 1837) however the distribution of both species overlaps in the area from the Celtic Sea to northwest Scotland (Griffiths et al., 2010). Material examined. Twenty-four eggcases were examined for this study. Most samples (n = 22) were removed from mature females that were captured by gillnet on the fishing grounds west of the Isles of Scilly (Bendall et al. , 2012). The remaining two eggcases examined were museum specimens collected from Scarborough (BMNH 1928.11.1.1–2). Two D. batis eggcases found on Perranporth Beach (northern Cornwall) in July 2014 were reported to the Great Eggcase Hunt in March 2015 (and identification confirmed from photographs), however they were not available for measurement. Description. The eggcase of D. batis (Figure 4 a) is a similar shape to that of D. cf. intermedia , however it is much smaller, with a mean total eggcase length of 211.9 ± 10.8 (193.0–235.0 mm), mean eggcase length of 139.7 ± 5.6 mm (129.0–150.0 mm), and mean eggcase width of 73.8 ± 3.6 mm (68.0–80.0 mm). Although only two historical specimens were examined, these were similar to the sizes recorded in contemporary samples. The capsule is convex on the dorsal side and flattened on the ventral side. Both surfaces are covered with a dense fibrous layer (which gives a bark-like appearance) with visible longitudinal striations (Figure 3 b), and the eggcase is pale brown in colour. Thin attachment fibres are often present on the margins. Keels are present but not always pronounced. Where the two sides meet at the margin, a slight groove is formed which runs the length of the capsule and fuses at the base of the horns on either end. Both the anterior and posterior aprons are broad and welldeveloped. The anterior horns protrude from the apron and curve in towards each other; they are relatively ...